Ionic Conductivity and Structural Analysis of 2-hyroxyethyl Cellulose Doped with Glycolic Acid Solid Biopolymer Electrolytes for Solid Proton Battery - M. A. Ramlli; N. A. A. Bashirah; M I N Isa (IOP Publishing, 2024)
Volume 440 International Fundamentum Science Symposium 2018 25–26 June 2018, Terengganu, Malaysia